Training and Quality Improvement of Tahsin Tartil Al-Quran Meisura Method for Santri Pondok Tahfiz Joglo Quran, Andong - Fiddarain, Zaduna; Harun, Makmur; Ismail, Faisal Husen; Butlam, Qoree; Marshal, Fahmi Dolles; Arfan, Fahmi; Nirwana, Andri (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2024)
The study of the Quran is a collective theme of a group of learning about the holy book of the Quran. Learning the Quran includes learning to read and write the Quran, learning tahsin tartil al-Quran (the science of Tajweed), learning to translate the Quran, learning to memorize the Quran (tahfidz), learning to interpret the Quran, and learning to practice the Quran. Rumah tahfidz is a non-formal education forum whose main orientation is learning to memorize the Quran (tahfidz). Learning tahfidz al-Quran will achieve the purpose of learning the Quran if supported by the stability of learning tahsin tartil al-Quran is qualified. The ability of students to memorize Quran readings will be influenced by their ability to apply tahsin tartil in learning to read the Quran. This urgency is behind the need for assistance and training in the Meisura method of tahsin tartil al-Quran to the students of Pondok Tahfiz Joglo Quran Andong, as a positive contribution to facilitate the learning of the Quran in general. The Meisura method is one of the latest tahsin tartil methods in making it easier for students to understand the Quran. The Meisura method departs from the pronunciation of the right letters (Makharij al-Surat), practicing quality reading, and chanting the Quran recitation with optimal tartil.